Analysis of Financial Reporting Accounting Information Systems at The Aceh Financial Services - Almira Keumala Ulfah; Yunina Yunina; Rahma Nurzianti; Rita Nengsih; Emilda Kadriyani (Institute of Computer Science (IOCS), 2021)
The accounting information system was implemented by the Aceh Financial Management Agency in 2008. The accounting information system used is the Regional Financial Management System (Sistem Manajemen Keuangan Daerah / SIMAKDA) application. Because this application has expired with the previous vendor, in 2012 the Aceh Financial Management Agency used a new accounting information system, namely Regional Financial Management Information System (Sistem Informasi Penelolaan Keuangan Daerah/SIPKD). In this study, because the data is presented in the descriptive form and describes what is contained in the Aceh Financial Management Agency, then the analysis of the problem uses qualitative analysis methods. Where after the data is obtained and processed, the data is analyzed and compared to further describe how far the suitability. The implementation of the Accounting Information system at the Aceh Financial Management Agency has been carried out a quite well-using computer equipment such as in making various forms and records, namely how to make cash and non-cash transaction proof forms. The application of the form is complete, accurate, and easy to understand.